PHYSICAL THERAPY IMPLICATIONS IN THE REHABILITATION OF NERVE COMPRESSION SYNDROME PATIENTS - Nela Tatiana BALINT (Editura Universitatii Transilvania din Brasov, 2019)
Nerve compression syndromes are medical conditions caused by direct pressure on a nerve; they manifest clinically through symptoms such as pain, diminished muscle strength, and paresthesias. Carpal tunnel syndrome is one of the most frequently encountered neuropathies nowadays, being also the most studied neuropathy of the hand because of is high prevalence, high social, medical, and economic costs. This paper presents a physical therapy intervention protocol for the rehabilitation of patients with nerve compression syndrome. The author also thinks that a treatment of this type is necessary for reestablishing the lost functions of the hand, especially the distal segment, but also for the socio-professional integration of the patient.